Contrasting lithospheric geophysical structure of the Black Sea subbasins: Relevance to testing geotectonic models for this mega depression - Rusakov, O.; Starostenko, V.; Pashkevich, I.; Kutas, R. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2023)
We present an integrated analysis of the geophysical parameters of the lithosphere of Black Sea basin obtained as a result of the interpretation of magnetic, gravity, thermal, deep seismic sounding and seismic-tomographic data. It first demonstrates inherent significant differences in geophysical parameters of lithosphere in the Western and Eastern Black Sea subbasins existing from the prerift stage. The set of reviewed parameters responsible for formation of the present-day lithosphere includes types of crust, depths to acoustic basement, configuration of subbasins, depths to Moho, heat flow and relief of the thermal-asthenosphere boundary (LAB), trends of main deep faults of the crystalline crust, their kinematic types, occurring linear magnetic anomalies, velocity pattern of subcrustal mantle. The above-mentioned parameters of the lithosphere are indicators of the age, geodynamics and driving mechanisms for opening of a subbasins. Oblique trends of the subbasins and the topography of Moho discontinuity in the west and east domains, oblique striking of pre-rifting Istanbul zone and the Shatsky Ridge and different trends of deep faults in the crystalline crust suggest distinct lithospheric structure existing from pre-opening of the Black Sea subbasins and different geodynamical conditions of its formation. The Odesa-Sinop-Ordu deep fault zone as a direct continuation of the Golovanivskaya suture zone of the Ukrainian shield and its slope, probably is of the Precambrian age. So it could be the tectonic boundary between two segments of pre-rift continental crust and between future subbasins. The examples illustrate how indicated parameters of the lithosphere can geophysically confirm the basic ideas of available models for geodynamics of the Black Sea.